2021
DOI: 10.21608/adjg.2021.50064.1321
|View full text |Cite
|
Sign up to set email alerts
|

Biological Pulp Response of Pulpine, Polyamidoamine Dendrimer and Their Combination in Dogs and their Remineralizing Effect on Carious Affected Human Dentin: A Randomized Clinical Trial

Abstract: Purpose: This study was conducted to evaluate the biological pulp response to Pulpine and Polyamidoamine Dendrimer and their combination in dogs and comparing their remineralizing potentials on human caries affected dentin. Materials and Methods: Forty-five teeth in 3 mongrel dogs were randomly divided into 3 groups according to the applied pulp capping material; group A1: Pulpine NE, group A2: PAMAM G3 and group A3: Pulpine and PAMAM. Class V cavities were prepared; the pulps were mechanically exposed and fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Besides drugs, G3 PAMAM was applied to mechanically exposed pulp teeth to act as a host substrate for pulpine. Clinical trials in 12 patients lasting one and a half years revealed that this gradual layering procedure, apart from more effective dentin mineralization, also enhanced the restoration of the injured pulp tissue [ 243 ].…”
Section: Applications Of Dendritic Polymers In Dentistrymentioning
confidence: 99%
“…Besides drugs, G3 PAMAM was applied to mechanically exposed pulp teeth to act as a host substrate for pulpine. Clinical trials in 12 patients lasting one and a half years revealed that this gradual layering procedure, apart from more effective dentin mineralization, also enhanced the restoration of the injured pulp tissue [ 243 ].…”
Section: Applications Of Dendritic Polymers In Dentistrymentioning
confidence: 99%